Sacral Anatomical Orientation in the Lebanese Population. (7th April 2020) - Maalouly, Joseph; Jabbour, Fouad; Saidy, Elias; Lati, Georgio; El-Hajj, Gerard; Aouad, Dany; Ayoubi, Rami; Nehme, Alexandre
Abstract : Introduction . PI is currently used as the gold standard measurement in spinopelvic anatomy. There is a need for a reliable method to calculate sacral anatomic orientation (SAO) independent of posture and to establish its association with PI, which was previously established in a single study (Peleg et al., 2007). Therefore, the aim of our study is the application and verification of this association on a Lebanese sample. Methods . Methods for measuring SAO and PI on living individuals are described. The study was carried out on 200 adult individuals using CT 3D images (volume-rendering method). Reliability (intratester and intertester) was evaluated using the intraclass correlation test. A regression analysis was carried out to evaluate the association between the two measurements. Results . There were 103 females (51%) and 97 males (49%) with a mean age of 58.68 ± 19.6 years (min = 20; max = 93). The mean SAO and PI in our population were found to be 52.65° (SD = 8.16°) and 59.08° (SD = 12.53°), respectively. SAO and PI measurements were highly correlated (Pearson correlation test; r  = −0.296, P < 0.0001 for our general population). PI can be predicted via SAO, i.e., SAO = (−0.193 × PI) + 64.057. Conclusions . SAO may be an important tool, alongside PI, in defining the sagittal shape of the spine and useful for understanding its association with spinal diseases as they are not affected by postural changes.